Diagnosis Miskonsepsi Siswa SMA di Kota Malang pada Konsep Suhu dan Kalor Menggunakan Three Tier Test - Sri Nurul Wahidah S.; Sentot Kusairi; Siti Zulaikah (Department of Physics Education, Universitas Mataram, 2016)
Misconception is one of the cause of students' learning difficulties, especially on physics. Misconceptions experienced by students needs to be diagnosed and its results used to improve learning. Its result should be delivered to students to help them learn better, so that these misconceptions can be corrected. In this regard, it should be developed diagnostic instruments which can provide information quickly and accurately one of them is a three-tier test. The aim of this study was to investigate whether the three-tier test able to identify student misconceptions. The sample of this study was 136 students of senior high school in Malang. Besides using written tests, interviews were conducted on several students to verify the results of the three-tier test. Conclusions of this study is the three-tier test that has been developed on Temperature and Heat topic is able to identify misconceptions students quickly and accurately.